2009
DOI: 10.1007/s10144-009-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of three‐site mutations in acetylcholinesterase and cytochrome P450 to genetic variation in susceptibility to organophosphate insecticides within a natural population of Drosophila melanogaster

Abstract: In this study, we attempted to elucidate the two resistance factors conferring resistance to organophosphates within the Katsunuma population of Drosophila melanogaster (Meigen), one of which has been mapped on the second chromosome and the other on the third chromosome. With regard to the second chromosome factor, we tested susceptibility to malathion of 54 recombinant inbred lines with recombination between ltd and vg. Analyses of variance (ANOVAs) showed highly significant variation in susceptibility to mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In the course of studies on genetic variation in resistance to OPs within the Katsunuma population, we have identified two resistance factors for OPs, one on chromosome 2 (~II-62) and the other on chromosome 3 (~III-50) [23]. The resistance factor mapped at ~II-62 on chromosome 2 was recently suggested to be a cytochrome P450, based on in vivo biochemical assays [15]. Other laboratories have provided the possibility that one or some cytochrome P450 (Cyp) genes around this map position might be involved in resistance to several insecticides including DDT [24,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of studies on genetic variation in resistance to OPs within the Katsunuma population, we have identified two resistance factors for OPs, one on chromosome 2 (~II-62) and the other on chromosome 3 (~III-50) [23]. The resistance factor mapped at ~II-62 on chromosome 2 was recently suggested to be a cytochrome P450, based on in vivo biochemical assays [15]. Other laboratories have provided the possibility that one or some cytochrome P450 (Cyp) genes around this map position might be involved in resistance to several insecticides including DDT [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Although Drosophila flies are not recognized as pest species, insecticide selection pressures have been imposed on the Katsunuma population of Drosophila melanogaster (Meigen), owing to management of other pest species [13]. In fact, the Katsunuma population of D. melanogaster exhibited genetic variation in susceptibility to OPs, which was composed of several resistance factors, including a resistant-type AChE and a cytochrome P450 [14,15]. Therefore, it is conceivable that various agents could mold genetic variation within the Katsunuma population, and that the effects of the fluctuations of genetic variation in OPEN ACCESS susceptibility to one class of insecticides within the population could also affect those to other classes of insecticides simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Using chromosome-substituted lines, we then identified two resistance factors, one at ~II-62 and the other at ~III-50 [17]. In addition to the fact that the resistance factor on chromosome III was mapped near the acetylcholinesterase locus (Ace, III-52; [18]), the target-site for organophosphate and carbamate insecticides, the resistant individuals having chromosome III from #1465-5 indeed showed ~15 times higher I 50 values (concentrations of chemicals that inhibit 50% of enzyme activity) for acetylcholinesterase (AChE) to fenitroxon (an organophosphate) than those from #451-10, suggesting that the resistance factor on chromosome III was one of the mutated AChEs, and that there were not any factors on other chromosomes contributing to the AChE activity [4]. On the other hand, the resistance factor on chromosome II was suggested to be a member of the cytochrome P450 gene, according to results from inhibition assays using a synergist, piperonyl butoxide [4].…”
Section: Resistance Factors For Organophosphates Within the Katsunumamentioning
confidence: 99%
“…In addition to the fact that the resistance factor on chromosome III was mapped near the acetylcholinesterase locus (Ace, III-52; [18]), the target-site for organophosphate and carbamate insecticides, the resistant individuals having chromosome III from #1465-5 indeed showed ~15 times higher I 50 values (concentrations of chemicals that inhibit 50% of enzyme activity) for acetylcholinesterase (AChE) to fenitroxon (an organophosphate) than those from #451-10, suggesting that the resistance factor on chromosome III was one of the mutated AChEs, and that there were not any factors on other chromosomes contributing to the AChE activity [4]. On the other hand, the resistance factor on chromosome II was suggested to be a member of the cytochrome P450 gene, according to results from inhibition assays using a synergist, piperonyl butoxide [4]. Therefore, it was suggested that one of the increased detoxification mechanisms as well as the target-site insensitivity contributed to resistance to organophosphates in the resistant line #1465-5, and that these resistance factors constructed at least a part of genetic variation in resistance to organophosphates within the Katsunuma population of D. melanogaster [4].…”
Section: Resistance Factors For Organophosphates Within the Katsunumamentioning
confidence: 99%
See 1 more Smart Citation